Trends in information-seeking behavior research at Airlangga University - Asma Rakha' Dinazzah; Rahmi Rahmi (Berkala Ilmu Perpustakaan dan Informasi, 2022)
Introduction. This study analyzes research trends in information-seeking behavior at Airlangga University, Indonesia. This study examines various aspects and models of information behavior using a systematic literature review. There has been an increase in research topics conducted by Airlangga University students, especially regarding information-seeking behavior. Data Collection Methods. The method used was a systematic literature review with a qualitative approach. Data sources were identified and accessed through the Airlangga University Repository (http://repository.unair.ac.id/). Items selected for review were 39 journal articles, 45 abstracts, and three theses. Data Analysis. The analysis process consist of planning, conducting, and reporting. 1) Creating research questions, 2) Conducting search process, 3) Deciding inclusion and exclusion criteria, 4) Conducting the quality assessment. Results and Discussion. Of all, there are 15 models of information-seeking behavior were examined. Among them, several frequently used models were those developed by Ellis; Leckie et al.; and Meho and Tibbo’s revision of Ellis. Conclusion. This research recommends the scientific development of information-seeking behavior, it is expected that research in Indonesia will create models of information-seeking behavior and be able to collaborate scientifically, increase innovation in knowledge and its application.